Ten years of modeling the Deepwater Horizon oil spill. (August 2021) - Ainsworth, C.H.; Chassignet, E.P.; French-McCay, D.; Beegle-Krause, C.J.; Berenshtein, I.; Englehardt, J.; Fiddaman, T.; Huang, H.; Huettel, M.; Justic, D.; Kourafalou, V.H.; Liu, Y.; et al.
Abstract: Since the 2010 Deepwater Horizon (DWH) oil spill, the Gulf of Mexico Research Initiative (GOMRI) has studied the oil spill from the perspectives of ocean environment, ecosystems, socioeconomics and human health. As GOMRI sunsets in its tenth year after the DWH oil spill, synthesis efforts recently took place to assess the accomplishments of the program. In this paper, we report on DWH modeling as part of GOMRI's Synthesis and Legacy effort. We compile a list of 330 published applications by GOMRI, the Natural Resource Damage Assessment (NRDA), and others studying the DWH oil spill and look at a wide range of subjects, tools, achievements, and integration with field research. We offer highlights and synthesis based on discussions and public webinars held in 2019 and 2020. We synthesize the significant achievements and advancements that have been made in integrating the various disciplines and domains from a modeling perspective. There was a large diversity of tools used, including at least 74 unique modeling systems. Most studies employed circulation models. These hydrodynamic models were often coupled to wave, river, and atmosphere models, as well as representations of high pressure physics and oil chemistry. Several research groups used Lagrangian transport models and statistical inference to track subsurface oil. Some coupled biophysical models were also employed to study oil fate and weathering, larval transport, biological effects, and population dynamics. In a few cases, such biophysical models were linked to marine populations and to humans through socioeconomics effects and ecosystem services. We consider models made for response planning and remediation, damage assessment, and restoration planning. There are relatively few socioeconomic or human health models, although those few examples make good use of biophysical modeling products. Our conclusions offer some insights on how the development of new tools has better prepared us for studying environmental management challenges in the Gulf of Mexico.